Strategies to Reduce Mortality Among Children Living With HIV and Children Exposed to HIV but Are Uninfected, Admitted With Severe Acute Malnutrition at Mulago Hospital, Uganda (REDMOTHIV): A Mixed Methods Study - Musiime, Victor; Kiggwe, Andrew; Beinomugisha, Judith; Kakooza, Lawrence; Thembo-Mwesige, Josam; Nkinzi, Sharafat; Naguti, Erusa; Atuhaire, Loice; Segawa, Ivan; Ssengooba, Willy; Mukonzo, Jackson K.; Babirekere-Iriso, Esther; et al. (Frontiers in Pediatrics, 2022)
Background: Children living with HIV (CLHIV) and children who are exposed to HIV but uninfected (CHEU) are at increased risk of developing malnutrition. Severely malnourished children have high mortality rates, but mortality is higher in CLHIV/CHEU. This study aims to investigate whether empiric use of an antibiotic with greater antimicrobial sensitivity (ceftriaxone) than standard-of-care (ampicillin plus gentamicin) will reduce mortality among CLHIV/CHEU admitted with severe acute malnutrition. Methods: This is an open label randomized controlled trial involving 300children; 76CLHIV and 224CHEU. The participants are being randomized to receive 1week of ceftriaxone (n= 150) or standard-of-care (ampicillin/gentamicin) (n=150), in addition to other routine care. The trial’s primary outcome is in-hospital mortality. Secondary outcomes are: length of hospitalization; weight-for-height, weight-for-age and height-for-age z-scores; and pattern/antimicrobial sensitivity of pathogens. In addition, 280 severely malnourished children of unknown serostatus will be tested for HIV at admission to determine the prevalence and factors associated with HIV-infection. Furthermore, all the CLHIV on LPV/r will each provide sparse pharmacokinetic (PK) samples to evaluate the PK of LPV/r among malnourished children. In this PK sub-study, geometric means of steady-state LPV PK parameters [Area Under the Curve (AUC) 0–12h, maximum concentration (Cmax) and concentration at 12 hours after dose (C12h)] will be determined. They will then be put in pharmacokinetic-pharmacodynamic (PK-PD) models to determine optimal doses for the study population Discussion: This study will ascertain whether antibiotics with higher sensitivity patterns to common organisms in Uganda and similar settings, will produce better treatment outcomes. The study will also provide insights into the current pattern of organisms isolated from blood cultures and their antimicrobial sensitivities, in this population. In addition, the study will ascertain whether there has been a significant change in the prevalence of HIV-infection among children presenting with severe malnutrition in the WHO recommended option B plus era, while determining the social/structural factors associated with HIV-infection. There will also be an opportunity to study PK parameters of antiretroviral drugs among severely malnourished children which is rarely done, and yet it is very important to understand the dosing requirements of this population. Trial registration: ClinicalTrials.gov; registration number - NCT05051163.